The Costs and Benefits of Migration into the European Union: Debunking Contemporary Myths with Facts - Ivo J. Leke; Simplice Asongu (African Governance and Development Institute (AGDI), 2016)
The purpose of this study is to dispel some myths associated with migrants in order to improve socio-economic appraisal of the consequences of the recent surge of migrants into Europe. We argue that: (i) the concern about loss of Christian cultural values is lacking in substance because compared to a relatively near historical epoch or era, very few European citizens do go to Church in contemporary Europe; (ii) the threat to European liberal institutions is falsifiable and statistically fragile because it is not substantiated with significant evidence; (iii) the insignificant proportion of the Moslem population that is aligned with Islamic fundamentalism invalidates the hypothesis on importation of radical Islamic fundamentalism and (iv) the concern about social security burden is relevant only in the short-term because of Europe's ageing population.
Keywords: F20; J61; J83; K31; O15; 330; Migration; the European Union; Development